A boy and his dog Staffel 1, Episode 8 = Ein Junge und sein Hund - Bloch, Robert 1917-1994; Bacon, Chris 1977-
A Boy and His Dog is a 1975 American black comedy science fiction film directed by actor L. Q. Jones, from a screenplay by Jones based on the 1969 novella of the same title by fantasy author Harlan Ellison. The film stars Don Johnson, Susanne Benton, Alvy Moore, and Jason Robards. It was independently produced and distributed by Jones' company LQ/Jaf Productions. The film's storyline concerns a teenage boy, Vic, and his telepathic dog, Blood, who work together as a team in order to survive in the dangerous post-apocalyptic wasteland of the Southwestern United States.
43 Min., farb.
Orig.: USA 2013